Simulation for Ruin Probabilities in Insurance with Sequence Autoregessive Dependence Random Variable (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this paper is used Monte Carlo methods to calculate an apporoximate ruin probabilities for classical risk processes with claim amounts are autoregessive process and generalized risk processes with premiums amounts, claim amountsare autoregessive processes.We build formulas for the algorithm and from there simulate illustrative numerical examples.